VIII.i Democratic Left-Labour Party Merger - Labour Party (Ireland); Democratic Left (Political Party : Ireland) (1999)
This series contains the records of the merger agreement between Democratic Left and the Labour Party in 1999. It includes: circulars to members; ‘Agreement on the union of the Labour Party and Democratic Left'; text of three speeches delivered on the occasion of the merger; copy of the Democratic Left constitution; draft and published copy of the ‘Democratic Programme; and joint working reports.